Densification of hydroxyapatite/zirconia nanocomposites fabricated via low-temperature mineralization sintering process and their mechanical properties - Yeongjun Seo; Shiori Nawa; Tomoyo Goto; Sunghun Cho; Tohru Sekino (Scientific Reports)
Abstract Hydroxyapatite/zirconia (HAP/ZrO2) composites were fabricated via the low-temperature mineralization sintering process (LMSP) at an extremely low temperature of 130 °C to enhance the mechanical properties of HAP and broaden its practical applications. For this purpose, 5–20 vol% calcia-stabilized ZrO2 were introduced into HAP, and HAP/ZrO2 nanoparticles, mixed with simulated body fluid, were densified under a uniaxial pressure of 800 MPa at 130 °C. At 10 vol% ZrO2, the relative density of the HAP/ZrO2 composite was determined to be 88.3 ± 1.1%. Additionally, it exhibited the highest values of mechanical properties such as the Vickers hardness (3.68 ± 0.18 GPa), fracture toughness (1.11 ± 0.10 MPa·m1/2), biaxial flexural strength (63.72 ± 2.35 MPa), and Young’s modulus (83.91 ± 1.93 GPa) among the composite samples. These values were considerably higher than those of the pure HAP matrix due to the adequate reinforcement by ZrO2 nanoparticles. Notably, owing to the low sintering temperature, phase decomposition of HAP, normally observed at high sintering temperatures above 1200 °C, was not observed. These results suggest that LMSP enables the incorporation of reinforcing ceramic materials with high sintering temperatures into bioactive materials at significantly lower temperatures, thereby improving their properties.